Health care system reform in developing countries - Wei Han (SAGE Publishing, 2012)
This article proposes a critical but non-systematic review of recent health care system reforms in developing countries. The literature reports mixed results as to whether reforms improve the financial protection of the poor or not. We discuss the reasons for these differences by comparing three representative countries: Mexico, Vietnam, and China. First, the design of the health care system reform, as well as the summary of its evaluation, is briefly described for each country. Then, the discussion is developed along two lines: policy design and evaluation methodology. The review suggests that i) background differences, such as social development, poverty level, and population health should be considered when taking other countries as a model; ii) although demand-side reforms can be improved, more attention should be paid to supply-side reforms; and iii) the findings of empirical evaluation might be biased due to the evaluation design, the choice of outcome, data quality, and evaluation methodology, which should be borne in mind when designing health care system reforms.